CHARACTER EDUCATIONAL VALUE IN NOVEL-NOVEL "HARRY POTTER"J. K. ROWLING WORKS - Puspitawati, Poppy Dewi; Emzir, Emzir; Akhadiah, Sabarti (IJLECR (International Journal of Language Education and Cultural Review), 2017)
The purpose of this research is to gain a deep understanding: 1) The novel structure consisting of theme elements, plot, background, characterization and the message contained in J.K. Harry Potter novels Rowling. 2) The values of character education that include mindset, behavior, attitude, creativity and interest in J.K. Harry Potter’s novels Rowling. And 3) The values of character education are viewed from the structural angle of hermeneutics contained in J.K. Harry Potter’s novels. Rowling. This research uses qualitative approach with content analysis method, through hermeneutic study based on textual hermeneutic and cultural hermeneutic. The findings of the overall research values of character education in J.K. Harry Potter’s novels Rowling’s review of hermeneutic studies consisted of: the pattern of pikers amounted to 46 or 58.9%, attitudes amounted to 68 or 94.35% behavior 51 or 53.7%, interest amounted to 30 or 44.6%, and creativity amounted to 42 or 48, 5%. Based on the above data can be concluded from the three of Harry Potter’s novels by J. K. Rowling the most is the attitude amounted to 68 or 94.35%. In the development of the story in J. K Rowling’s Harry Potter novels emphasizes attitude. Meanwhile, the value of education as the least interest emerging amounted to 30 or 44.6%.